ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN MASYARAKAT KOTA TANJUNGBALAI - Adilman Baradarkhasan Zega; Tiarma Br Manurung; Dede Ruslan; Raina Linda Sari (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2023)
Welfare is a very important element in life. Referring to the meaning of welfare in general terms, welfare refers to a good condition, a human condition where people are in a state of prosperity, in a state of health and peace. Welfare is a measuring point for a community that is already in a prosperous condition. The level of welfare in Tanjungbalai City which is known to be still low and the factors that influence it are the low level of education, the low level of community income, and the level of financial literacy that is not yet high. So the problem formulation of this research is how the influence of education, income, and financial literacy on community welfare in Tanjungbalai City, North Sumatra. This study uses quantitative descriptive research methods with the population used is the people of Tanjungbalai City who are over 20 years old with a total of 108,177 people, the number of samples used is 100 people with purposive sampling technique. The results of the study through the significance test show that the variables of education, income, and financial literacy individually and together affect the welfare variable in Tanjungbalai City.